INTERNET OF THINGS UNTUK MONITORING TANAMAN FLORIKULTURA BERBASIS MOBILE - Pratama, Muhammad Urfan Adjie; Ikrimach, Ikrimach (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
The development of monitoring applications in the field of floriculture is necessary to improve the quality of ornamental plants. Keeping up with the advancements in Internet of Things technology for detecting growing media conditions, an efficient monitoring solution is needed to optimize the growth, care, and productivity of plants. This research aims to create a mobile-based floriculture plant monitoring application that is expected to assist plant cultivators in observing the microenvironmental conditions of plants, measuring soil moisture, air humidity, and light received by the plants to detect potential issues such as pest infestations or diseases. Thus, the research and development of this application are expected to support the floriculture industry in enhancing plant quality, production efficiency, and environmental sustainability, making it an essential part of modern sustainable cultivation. This research will result in a mobile application built using the Flutter framework, designed to be more flexible for real-time monitoring, especially for Aglaonema plants, using the Waterfall development method. This application can detect not only Aglaonema plants but also other floriculture plants like Chrysanthemums and other ornamental plants. The application has been tested using the Blackbox method, and the test results indicate that the application performs well in monitoring the temperature, soil moisture, and air humidity of Aglaonema plants, sending data to the server, and displaying it on the application quickly and efficiently.